Deep Transformation toward Decoloniality in Social Work: Themes for Change in a Social Work Higher Education Program. Issue 2 (3rd May 2020) - Harms Smith, Linda; Rasool, Shahana
ABSTRACT: This article describes thematic outcomes of a process of engagement around deep transformation toward Decoloniality in a university social work education program. Given the gravity of working toward Decoloniality for social work education in South Africa, it was critical to theorize about this process. Current South African realities evidence ongoing structures of Coloniality and Apartheid which permeate all spheres, not least the domains of knowledge, power, and relationships in higher education. However, a narrow interpretation of Decoloniality relating only to 'curriculum' or 'indigeneity' as potential for change, is problematic. Ignoring material realities of ongoing Coloniality perpetuates the very oppressive structures it seeks to overcome and so depth transformation which engages with all levels of a social work education program is required. This article engages with thematic areas that emerged and which shaped work toward Decoloniality, among social work educators at one higher education department. These included domains for engagement with Decoloniality (theorists; pedagogy; educators; learners; content; research and discourse; context) and principles for such work (Afrika as the center; attention to power dynamics; race, class, and gender; acknowledgment of structural issues; critical conscientization and voice; Ubuntu). These thematic areas now form the basis of the new social work program at the University.